Malcolm lives! : the official biography of Malcolm X for young readers - Kendi, Ibram X. (Farrar Straus Giroux, 2025)
"Compiling the definitive speeches, sermons, and correspondence as well as some never-before-seen original material, this comprehensive narrative biography of American icon, Malcolm X, will be the definitive reference volume for young readers"--